Efektivitas Model Pembelajaran Treffinger dengan Pendekatan Saintifik terhadap Kemampuan Berpikir Tingkat Tinggi Siswa Kelas VIII SMP - Awi Dassa; Dinar; Reni (Issues in Mathematics Education (IMED), 2020)
This research aims to determine effectiveness of treffinger learning model with scientific approach to student’s higher order thinking skills of grade VIII SMP by referring to effectiveness of learning, namely students' higher order thinking skills, student activities, and student responses. This research is pre-experimental study with quantitative approach and sampling technique used is cluster random sampling. Data analysis technique used is descriptive and inferential analysis techniques. Results of descriptive analysis showed: (1) average results of students' pretest was 31.10 (bad category), average student posttest result was 54.22 (good enough category) (2) the posttest results showed that classical completeness was reached at 100% (21 students) achieved individual completeness, (3) average normalized gain was 0.33 (medium category), (4) average student activity was 3.67 (very good category), (5) average percentage of students who gave positive response of 92.06%. Inferential analysis results show: (1) average value of higher order thinking skills of students taught with treffinger learning models with scientific approach greater than 40 (good enough category), (2) average normalized gain value is greater than 0,3 (medium category), (3) there is a significant increase in learning outcomes on students' higher order thinking skills before and after application of treffinger learning model with scientific approach. From the results of this study it can be concluded that learning by applying the Treffinger learning model with scientific approach is effectively applied to students of grade VIII SMP.